Correction: LRRK2 dynamics analysis identifies allosteric control of the crosstalk between its catalytic domains. - Jui-Hung Weng; Phillip C Aoto; Robin Lorenz; Jian Wu; Sven H Schmidt; Jascha T Manschwetus; Pallavi Kaila-Sharma; Steve Silletti; Constanza Torres-Paris; Sebastian Mathea; Deep Chatterjee; Stefan Knapp; et al. (PLoS Biology)
[This corrects the article DOI: 10.1371/journal.pbio.3001427.].